ANALISIS PERAMALAN PENDAPATAN DESA SEBAGAI ASESMEN PENDIRIAN BADAN USAHA MILIK DESA (BUMDES) PEMBIAYAAN SYARIAH DI DESA GUNUNG MENYAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Oktavani, Sella; Thantawi, Tubagus Rifqy; Mursyidah, Azizah (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2024)
This study aims to determine village income in the attitude of BUMDES which finance sharia and analyze forecasting of village income in the attitude of BUMDES which finance sharia in Gunung Menyan Village, Pamijahan District. The subject of this research is BUMDES Gunung Menyan Village, Pamijahan District, Bogor. In this study using the method The research method used in this study is the Quantitative forecasting method is a forecasting method that uses mathematical calculations in its calculations. The types and sources of research data are using primary data and secondary data. the results of forecasting or predictions that have been calculated using the seller model Linear Trend, Quadratic Trend and Exponential Trend are the predicted results of the final Linear Trend. 94813001.1, or rounded up to Rp. 94,813,001, the Quadratic Trend prediction result is Land and Building Tax Receipts in 2024 which is estimated at 171961420.9, or rounded up to Rp. 171,961,420, while the Exponential Trend prediction result is Land and Building Tax Receipts in 2024 is estimated at 22728013.9, or rounded up to IDR 22,728,013.